Financial Fragility and the Structure of Financial Markets - Jan A. Kregel (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1993)
This paper investigates the role of financial stucture on he financial fragility of the economy. It argues that while strucures is indipendent of the degree of what Misky calls financial fragility, it will have an impact on the rate of contagion by which financial fragility produces general economic instability. This is independent of the traditional view of instability as being caused by financial intermediation creating a mismatch of maturities of financial institutions' asset and liabilities, but is linked to the quality of the assets against which banks lend when there is a rapid increase in resources intermediated by banks. It concludes by arguing that the present system has become more prone to financial crises because of an increase in the speed of contagion due to a change in the financial structure.
Keywords: 330